The Journal of Abnormal Psychology, Volume 10 - Various (Salt Lake City, UT : Project Gutenberg, 1998)
"The Journal of Abnormal Psychology, Volume 10" by Various is a scientific publication written during the early 20th century. This volume presents a collection of original articles and analytical studies focusing on various aspects of abnormal psychology, including hysteria, dream analysis, and psychoneuroses. The beginning of this journal delivers insightful discussions and case studies that explore the complexities of psychological conditions, particularly emphasizing hysteria as a means of exerting agency in interpersonal relationships. Articles from contributing authors$1 (Bincluding a detailed analysis of a woman's hysteria linked to marital conflicts$1 (Breveal how emotional distress can manifest physically. Additionally, the opening portion introduces multiple perspectives on dream interpretation, showcasing how dreams can serve as gateways to understanding deeper psychological issues. Overall, this opening is rich with clinical observations and theoretical explorations that set the stage for a broader discussion on the motivations and mechanisms underlying various psychological phenomena. (This is an automatically generated summary.)s
Release date is 1998-03-01
Scanned by Charles Keller with OmniPage Professional OCR software
Keywords: Psychology, Pathological -- Periodicals; Psychology -- Periodicals; Social psychology -- Periodicals